2014
DOI: 10.3109/19401736.2014.926499
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the whitetip reef shark Triaenodon obesus (Carcharhiniformes: Carcharhinidae)

Abstract: The complete mitochondrial genome of the whitetip reef shark Triaenodon obesus is determined in this study. It is 16,700 bp in length, with the typical gene composition, arrangement and transcriptional orientation in vertebrates. The overall base composition is 31.4% A, 25.8% C, 13.2% G and 29.7% T. Two start codons and two stop codons are found in the protein-coding genes. The 22 tRNA genes ranged from 67 to 75 nucleotides. The tRNA-Ser2 lost the DHU arm and could not be folded to the typical cloverleaf secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The ‘DHU’ arm of this tRNA was a large loop instead of the conserved stem-and-loop structure. Due to a representative characteristics 41 , it was also observed in other Chondrichthyes mtDNA, including Chiloscyllium griseum 42 T. obesus 37 and so on. Fifteen of the tRNA genes were each observed to have at least one G-T mismatches in their respective secondary structures, which forming a weak bond.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The ‘DHU’ arm of this tRNA was a large loop instead of the conserved stem-and-loop structure. Due to a representative characteristics 41 , it was also observed in other Chondrichthyes mtDNA, including Chiloscyllium griseum 42 T. obesus 37 and so on. Fifteen of the tRNA genes were each observed to have at least one G-T mismatches in their respective secondary structures, which forming a weak bond.…”
Section: Resultsmentioning
confidence: 96%
“…Seven of 13 PCGs ( ND1 , COXI , ATP8 , COXIII , ND4L, ND5 , ND6 ) used a typical TAA termination codon, which was typical for Carcharhiniformes mtDNA 35 , 36 ; whereas COXII , ND3 and ND4 terminated with a single T and ATP6 , ND2 and Cytb terminated with TA (Table 1 ). It was akin to sequenced mtDNA of Carcharhiniformes, including Triaenodon obesus 37 , Carcharhinus macloti 38 , Mustelus griseus 39 , S. canicula 25 and C. acronotus 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Although any change in tRNA secondary structure could potentially alter its amino acid recognition capability (Nwobodo et al 2019), it has been shown that loss of the D arm does not necessarily imply reduced functionality; in fact, almost all tRNAs Ser for AGY/N codons lack the D arm, and truncated tRNAs appear to have been compensated for by several interacting factors (Watanabe et al 2014). Furthermore, among fishes, loss of the tRNA Ser D arm is not unique to O. infernale, for it has been reported in several species, including chondrichthyans such as Chiloscyllium griseum (Chen et al 2013), Triaenodon obesus (Chen et al 2016), and Cephalloscyllium umbratile (Zhu et al 2017), as well as teleosts such as Oreochromis andersonii and O. macrochir (Bbole et al 2018). Although most tRNAs present the canonical 7-bp T loop, nonstandard T-loop lengths were observed in tRNA Met (6 bp), tRNA Phe (8 bp), and tRNA Ser (9 bp).…”
Section: Transfer and Ribosomal Rnasmentioning
confidence: 99%